Developing a hybrid filter structure and a control algorithm for hybrid power supply - Yuriy Anatolievich Sychev; Maxim Evgenievich Aladin; Serikov Vladimir Aleksandrovich (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The paper presents the results of a study on hybrid filter operation and performance under hybrid power supply. In the study, a hybrid filter structure was developed and proved to perform a set of power quality improving functions. The paper demonstrates that it is necessary for the hybrid filter structure to be variable in order to adapt to changes in power supply. A case is made for using an additional passive filter at the active part output of the hybrid filter under distributed generation. The optimal structure and parameters of such an additional passive filter are identified and proved. Based on the experimental research results, the mathematical and computer simulation models of the proposed hybrid filter for hybrid power supply were developed. The modeling and simulation results showed the efficiency level to be satisfactory and power quality to improve due to applying the proposed hybrid filter. Using the modeling and simulation results, an adaptive algorithm to control the operation factors of the proposed hybrid filter under hybrid power supply was developed, tested, and evaluated. Practical recommendations for industrial application of the proposed hybrid filter are given.